Associations of Hearing Sensitivity, Higher-Order Auditory Processing, and Cognition Over Time in Middle-Aged Adults - Merten, Natascha (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Age-related hearing loss (impairment in hearing sensitivity and/or higher-order auditory processing) and cognitive decline are common co-occurring impairments in elderly adults. Their relation in the process of aging remains insufficiently understood. We aim to assess the temporal relations of decline in hearing sensitivity, higher-order auditory processing, and cognition in middle-aged adults. METHODS: This study included 1,274 Beaver Dam Offspring Study participants who participated in three examinations (baseline, 5-year, and 10-year follow-up). We assessed hearing sensitivity through pure-tone audiometry (PTA, averaged thresholds of 0.5, 1, 2, 4 kHz of the better ear), higher-order auditory processing as word recognition in competing message (WRCM) using the Northwestern University 6 word list in the better ear, and cognition through trail-making test performance (TMT). Linear mixed-effects models and linear regression models were used to determine associations over time and to what extent these measures influence each other over time. RESULTS: The longitudinal decline between all functions was associated with the strongest relationships between PTA and WRCM. The effect of baseline PTA on WRCM 10 years later (standardized ß = –.30) was almost twice as big as the effect of baseline WRCM on PTA 10 years later (standardized ß = –.18). The effect of baseline WRCM on TMT 10 years later and vice versa were small (standardized ß = –.05). No directional relationship between PTA and TMT was identified (standardized ß ≤ .02). CONCLUSIONS: While hearing sensitivity might affect higher-order auditory processing, associations between hearing and cognition appear bidirectional and weak in midlife. We need to be cautious before inferring causal effects of hearing on cognition.